Формування та розвиток економіко-управлінського інструментарію забезпечення бізнес-процесів - Шуляр, Роман Віталійович (Національний університет "Львівська політехніка", 2019)
У дисертації запропоновано вирішення науково-прикладної проблеми формування економіко-управлінського інструментарію, розвитку на його основі теоретико-методологічних підходів до розвитку гнучких та адаптивних систем управління бізнес-процесами з метою забезпечення їх якості на підприємствах. Економіко-управлінський інструментарій менеджменту бізнес-процесів підприємств, сформований на основі підходів щодо гнучкого реагування бізнес-процесів на зміни внутрішнього та зовнішнього середовищ, оцінювання потреб адаптування системи менеджменту, тобто, потреб впровадження нових підходів, дозволяє вийти на нові показники якості бізнес-процесів, виявляти негативні сторони їх протікання та скеровувати у більш ефективне русло. Для цього у дисертацій розроблені показники для моніторингу та оцінювання бізнес-процесів та їх якості, моделі, які ураховують показники ефективності планованих зміни у системі менеджменту, її адаптування у разі настання подій, чинників, явищ та умов, які система на основі наявного інструментарію не здатна подолати і потребує змін з метою подолання відхилень у діяльності підприємства. В диссертации предложено решение научно-прикладной проблемы формирования экономико-управленческого инструментария, развития на его основе теоретико-методологических подходов к формированию гибких и адаптивных систем управления бизнес-процессами с целью обеспечения их качества на предприятиях. Экономико-управленческий инструментарий менеджмента бизнес-процессов предприятий, сформированный на основе подходов к гибкого реагирования бизнес-процессов на изменения внутренней и внешней среды, оценки потребностей адаптации системы менеджмента, то есть, потребностей внедрения новых подходов, позволяет выйти на новые показатели качества бизнес процессов, выявлять негативные стороны их протекания и направлять в более эффективное русло. Для этого в диссертации разработаны показатели для мониторинга и оценки бизнес-процессов и их качества, модели, которые учитывают показатели эффективности планируемых изменениях в системе менеджмента, ее адаптации в случае наступления событий, факторов, явлений и условий, система на основе имеющегося инструментария не способна преодолеть и требует изменений с целью преодоления отклонений в деятельности предприятия. The thesis proposes the solution of the scientific and applied problems of the formation of economic and managerial instruments, the development on the basis of the theoretical and methodological approaches to insurance of flexible and adaptive business process management systems in order to increasing their quality at the enterprises. The actuality of this scientific problem and the study of the ways of its solution is confirmed by the results of the analysis of the current stage of development of business structures and the conditions of their dynamic and fast changing economic activity in the conditions of increasing the need for investment attractiveness and the influence of European integration processes. The identified trends in the corporative management require an active response to this environment dynamic of the, and flexible and adaptive managerial approaches must help to forecast changes and rebuild the business process management system for effective function, to provide qualitative and quantitative indicators achievement. Economic and management instruments for management of business processes of enterprises was formed on the basis of methodical approaches to flexible response of business processes to changes in the internal and external environment, assessment of the needs of adapting the management system, the needs for the introduction of new methodological approaches. They allow to get new indicators of quality business-processes to identify the negative aspects of their flow and to guide them in a more efficient way. According to this, in the theses have been developed indicators of the effective monitoring and evaluation of business-processes and their quality, which take into account the of the planned changes in the management system, its adaptation in events, factors and conditions witch that the system, based on existing instruments, cannot overcome and needs changes in order to deviations in the activities of the enterprise. The economic and managerial instruments for business process management in the enterprise management system are the arsenal of support for flexibility, adaptability and quality assurance of business processes. Developed, grounded and offered instruments in the thesis are an integral part of the modern enterprise management system in the context of attention to their business processes. Such instruments are aimed fast of all at timely recognition, decreasing the harmful effects of the environment and the internal environment in the enterprise, overcoming the deviations in qualitative and quantitative indicators of effectiveness of business processes. During process of the research it was discovered that the most common set of business process expectations for development parameters does not provide the effective result in terms of the effectiveness of their management. These processes set the task of monitoring the processes of their implementation in the best and precise way using monitoring, monitoring quality indicators, reviewing and comparing the basic business process models based on the concept of benchmarking, systematically optimizing management decisions in the quality management system, ranking business processes for the importance of vertical integration indicators, the creation of a competitive environment at the entrance of business processes and flexible management of quality options. In addition to the classic methods of managing business processes based on their modeling, reengineering and quality management, the economics and management instruments developed in the thesis focus management attention on such parameters as flexibility and adaptability of business processes as ways of ensuring the quality of their results. The formation of economic and managerial instruments in the system of business process management in practical activity provide sectors of quality, flexibility and adaptability of business processes. These sectors are connected by intermediate stages of monitoring of target indicators. Formed structural and logical model of the formation and development of economic and managerial instruments for business process support provides an opportunity to distinguish the signs of flexibility and adaptability of quality management. The rankings of the indicators of the quality of business processes for internal and external customers in relation to the enterprise and the study of the characteristics of the change in quality indicators due to the flexibility and adaptability of the quality management system based on expert surveys have allowed to determine key indicators of quality, flexibility and adaptability of business processes of enterprises. According to the survey of specialists at the investigated enterprises, the dependence of the factors of decision-making in the sphere of quality has been determined, namely, the need for financing can determine the effect of the decisions. This effect besides the level of financing depends on the time of getting this effect because the time increases the need for investment. These factors allowed identifying the types of games theory which can be modeled in quality groups for optimizing managerial decisions and options for setting tasks for application of game theory to optimize the solution in the quality management system of business processes. The estimation of quality assurance methods in an example with a machine-building enterprise for forming a mixed form of optimization game was conducted and a game matrix was constructed for choosing a solution based on the priority of time and material costs for its implementation, as well as the matrix of the game for choosing a solution based on the ratio of product reliability to time consumption and material costs for its implementation. On the basis of these matrices the variants of the decision on basis on the game theory in the chosen methods in a group on the quality of business processes are formed and evaluated. In order to overcome inaccuracies in the evaluation of decisions based on the developed recommendations, the classification of quality problems and their impact on the formation of quality groups has been conducted. On the basis of this classification of quality problems and deviations can be possible to formulate the sequence of actions, instructions on the actions of the quality management system and attitudes towards solving problems and overcoming these abnormalities. Some problems may go beyond the competence of field managers, so they can be solved only on the basis of the work of a collegial body – groups of quality.
Формирование и развитие экономико-управленческого инструментария обеспечения бизнес-процессов
Formation and development of economic and managerial instruments for business process support
Keywords: бізнес-процеси; економіко-управлінський інструментарій; управління; забезпечення якості; гнучкість; адаптивність; бизнес-процессы; экономико-управленческий инструментарий; управления; качества; гибкость; адаптивность; business processes; economic and managerial instruments; management; quality assurance; flexibility; adaptability; 338.4:658]:005.2(043.5)